Mitochondrial membrane potential-based genome-wide RNAi screen of Trypanosoma brucei - Verner, Zdenek; Paris, Zdenek; Lukes, Julius (Parasitology research, 2010)
We have screened the Trypanosoma brucei genome-wide RNAi library by staining the procyclics with the dye JC-1 followed by sorting the differentially stained cells by flow cytometry. This allowed us to highly enrich for cells in which mitochondrial membrane potential was decreased. We have further validated a subset of selected clones by a reverse approach in which we showed that cloning the selected genomic regions into another RNAi vector also results in a drop in mitochondrial membrane potential.
Keywords: genový knockdown; Flow Cytometry; genom protozoální; malá interferující RNA; Genome, Protozoan; průtoková cytometrie; zvířata; Humans; Membrane Potential, Mitochondrial; membránový potenciál mitochondrií; Trypanosoma brucei brucei; RNA, Small Interfering; Gene Knockdown Techniques; lidé; Animals